Potensi Spin Off dan Konversi pada Pengembangan Bank 9 Jambi Syariah - Nisya Adella Jaya; Bahrul Ma’ani; Addiarrahman Addiarrahman (Pusat Riset dan Inovasi Nasional, 2025)
This qualitative study aims to explore the key challenges and opportunities in the spin-off process of the Sharia Business Unit (UUS) at Bank 9 Jambi Syariah. The research was conducted at Bank 9 Jambi Syariah located on Jalan Lintas Sumatera, Telanaipura District, Jambi City, by gathering information from leaders and employees, including the Director, Sharia Supervisory Board, Head of Corporate Secretary, Head of Sharia Division Operations, Head of Operations, and Monitoring and Budgeting staff. The findings indicate that asset and capital readiness remain the main obstacles hindering the implementation of the spin-off. Despite this, the human resources within the Sharia Business Unit are considered adequate, supported by employees with educational backgrounds in sharia studies and training related to sharia banking fundamentals. The study emphasizes that the spin-off process cannot be executed easily; it requires comprehensive strategies and strong preparation to achieve successful separation. The primary challenges faced by Bank 9 Jambi include substantial capital requirements and internal organizational readiness, which align with common issues experienced by conventional banks attempting similar transformations. Based on the interviews and an assessment of regulatory obligations stated in the Sharia Banking Law, the decision to carry out a spin-off must be carefully evaluated by the parent conventional bank. Bank 9 Jambi also takes into account profit potential, as the spin-off is projected to provide operational independence and enhance customer comfort. These considerations form the basis of strategic planning for the future of the UUS at Bank 9 Jambi.